2018
DOI: 10.4103/ejd.ejd_124_18
|View full text |Cite
|
Sign up to set email alerts
|

Can probiotic cleaning solutions replace chemical disinfectants in dental clinics?

Abstract: Objectives:We aim to assess the antibacterial effectiveness of probiotic cleaning in a dental clinic at the University Dental Hospital Sharjah (UDHS), UAE.Materials and Methods:The current cleaning protocol of UDHS was evaluated by the surface swabbing of three dental clinics routinely cleaned using regular chemical disinfectants. Then, a new probiotic cleaning solution containing Bacillus subtilis was applied for 3 weeks in a selected clinic. Bacteria were grown onto selective culture media for colony countin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…People who are using the elevators should put their masks in a correct way and evade direct contact with buttons and other objects. 2 , 23 , 24 …”
Section: Disinfection and Sterilization Protocolmentioning
confidence: 99%
“…People who are using the elevators should put their masks in a correct way and evade direct contact with buttons and other objects. 2 , 23 , 24 …”
Section: Disinfection and Sterilization Protocolmentioning
confidence: 99%
“…Another line of thought regarding the control of the microbiological quality of water in DUWL could be its biocontrol. Indeed, some microbial-based cleaning solutions showed interesting effects in the reduction of healthcare-associated infection-related pathogens [34], especially on the surfaces of a dental clinic [35]. In the same way, studies showed that predatory bacteria with protective features could be used as agents to prevent recolonization of the periodontal pocket by pathogenic germs after treatment [36].…”
Section: Discussionmentioning
confidence: 99%
“…118,127 Although several studies found correlations between the use of probiotic cleaning solutions and reductions in hospital-acquired infections, a vital part of their reasoning is missing: longevity. As food additives, microorganisms or genes.…”
Section: Pro -Microb Ial Cle Aningmentioning
confidence: 99%
“…Rather, they appeared to kill or outcompete the other bacterial cells to ingest the antimicrobial resistance (AMR) genes. 118,127 Although several studies found correlations between the use of probiotic cleaning solutions and reductions in hospital-acquired infections, a vital part of their reasoning is missing: longevity.…”
Section: Further Environmental Context Can Alter Microbial Communitiesmentioning
confidence: 99%